High-Dose Epinephrine Enhances Platelet Aggregation at the Expense of Procoagulant Activity - Aliotta, Alessandro; Bertaggia Calderara, Debora; Zermatten, Maxime G.; Alberio, Lorenzo (Thrombosis and Haemostasis, 2021)
Platelet activation is characterized by shape change, granule secretion, activation of fibrinogen receptor (glycoprotein IIb/IIIa) sustaining platelet aggregation, and externalization of negatively charged aminophospholipids contributing to platelet procoagulant activity. Epinephrine (EPI) alone is a weak platelet activator. However, it is able to potentiate platelet activation initiated by other agonists. In this work, we investigated the role of EPI in the generation of procoagulant platelets. Human platelets were activated with convulxin (CVX), thrombin (THR) or protease-activated receptor (PAR) agonists, EPI, and combination thereof. Platelet aggregation was assessed by light transmission aggregometry or with PAC-1 binding by flow cytometry. Procoagulant collagen-and-THR (COAT) platelets, induced by combined activation with CVX-and-THR, were visualized by flow cytometry as Annexin-V-positive and PAC-1-negative platelets. Cytosolic calcium fluxes were monitored by flow cytometry using Fluo-3 indicator. EPI increased platelet aggregation induced by all agonist combinations tested. On the other hand, EPI dose-dependently reduced the formation of procoagulant COAT platelets generated by combined CVX-and-THR activation. We observed a decreased Annexin-V-positivity and increased binding of PAC-1 with the triple activation (CVX + THR + EPI) compared with CVX + THR. Calcium mobilization with triple activation was decreased with the higher EPI dose (1,000 µM) compared with CVX + THR calcium kinetics. In conclusion, when platelets are activated with CVX-and-THR, the addition of increasing concentrations of EPI (triple stimulation) modulates platelet response reducing cytosolic calcium mobilization, decreasing procoagulant activity, and enhancing platelet aggregation.
Keywords: platelets; procoagulant platelets; epinephrine; aggregation